A potential role for mechanical forces in the detachment of podocytes and the progression of CKD - Kriz, Wilhelm; Lemley, Kevin V. (Journal of the American Society of Nephrology, 2014)
Loss of podocytes underlies progression of CKD. Detachment of podocytes from the glomerular basement membrane (GBM) rather than apoptosis or necrosis seems to be the major mechanism of podocyte loss. Such detachment of viable podocytes may be caused by increased mechanical distending and shear forces and/or impaired adhesion to the GBM. This review considers the mechanical challenges that may lead to podocyte loss by detachment from the GBM under physiologic and pathophysiologic conditions, including glomerular hypertension, hyperfiltration, hypertrophy, and outflow of filtrate from subpodocyte spaces. Furthermore, we detail the cellular mechanisms by which podocytes respond to these challenges, discuss the protective effects of angiotensin blockade, and note the questions that must be addressed to better understand the relationship between podocyte detachment and progression of CKD.